Copper-catalyzed oxidative cyclization of vinyl azides with benzylic Csp3–H bonds for the synthesis of substituted phenanthridines. Issue 41 (26th September 2016) - Yang, Jun-Cheng; Zhang, Jin-Jiang; Guo, Li-Na
Abstract : A copper-catalyzed oxidative cyclization of vinyl azides with benzylic Csp 3 –H bonds via a tandem dual C–H functionalization process has been developed. This reaction allows access to substituted phenanthridines containing a variety of functional groups. Abstract : A copper-catalyzed oxidative cyclization of vinyl azides with benzylic Csp 3 –H bonds via a tandem dual C–H functionalization process has been developed. This procedure allows access to substituted phenanthridines containing a variety of functional groups. In addition to benzyl hydrocarbons, other substrates containing unactivated Csp 3 –H bonds, such as ethers and alkanes could also be applied successfully to this transformation.